Desenvolvimento de um bioprocesso utilizando-se resíduos para produção de amilases por Rhizopus oligosporus e etanol por Saccharomyces cerevisiae - Correa, Fabiane Fernanda de Barros [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Amylases are enzymes belonging to the class of hydrolases acting on starch structure with the hydrolysis of glycosidic bonds of α-1,4 and α-1,6 types, in the interior of the chains of amylose and amylopectin, respectively. Currently they are responsible for about 30% of the world market enzymes and show a wide range of industrial applications. Fungi capable of producing amylases can grow by low cost inputs in solid-state fermentation (SSF), which enables the recovery of the agricultural industry by-products and provides support similar to that found by the microrganism in the natural environment. This study aims to produce amylase by Rhizopus microsporus var. oligosporus in solid-state fermentation using wheat bran as substrate partially to purify the crude enzyme extract obtained biochemically characterize the partially purified enzyme extract and subsequently to carry out the hydrolysis saccharification of starch present in broken rice and fermentation of it by Saccharomyces cerevisiae for ethanol production. Enzymatic activity of the raw extract was 39.8 U/mL equivalent to 358 U/g substrate. The purification ratio after the chromatography step was partial, but sufficient for the biochemical characterization of the produced extract was taken. These tests showed optimal range of pH 4.0 to pH 5.5 indicating the acidic condition as the best for this study. The pH stability was wide range of pH 3.5 to pH 8.5 with 40 to 60% relative activity. The optimum temperature for enzyme activity determined as optimum was 60 to 65 °C, but the enzyme was thermostable up to 60 °C. Ion effect of the amylolytic enzyme tests showed that the reaction Cu+2, Zn+2, Al+2 and Na+2 ions behaved like activity inhibitors. The Mn+2 ions distinguished for enhancing at about 60% relative enzymatic activity to hydrolysis without addition of ions. The enzymatic hydrolysis of broken rice using as substrate allowed the complete conversion of starch to reducing sugars ...

As amilases são enzimas pertencentes à classe das hidrolases, atuando na estrutura do amido com a hidrólise das ligações glicosídicas dos tipos α-1,4 e α-1,6, do interior das cadeias de amilose e amilopectina, respectivamente. Atualmente são responsáveis por cerca de 30% do mercado mundial de enzimas e apresentam uma vasta gama de aplicações industriais. Os fungos capazes de produzir enzimas amilolíticas podem ser cultivados mediante insumos de baixo custo empregados na fermentação em estado sólido (FES), o que possibilita a valorização dos subprodutos da agroindústria, bem como fornece suporte semelhante ao encontrado pelo micro-organismo no ambiente natural. O presente estudo visa produzir amilases por Rhizopus microsporus var. oligosporus em FES utilizando o farelo de trigo como substrato, purificar parcialmente o extrato bruto enzimático obtido, caracterizar bioquimicamente o extrato enzimático parcialmente purificado e posteriormente realizar a sacarificação pela hidrólise do amido presente na quirera de arroz e fermentação alcoólica por Saccharomyces cerevisiae para produção de etanol. A atividade enzimática do extrato bruto foi 39,8 U/mL o que equivale a 358 U/g de substrato. O índice de purificação, após as etapas de cromatografia foi parcial, mas suficiente para que a caracterização bioquímica do extrato produzido fosse realizada. Estes testes demonstraram faixa ótima no pH 4,0 e pH 5,5, indicando as condições ácidas como as melhores para este estudo. A estabilidade do pH foi ampla variando do pH 3,5 ao pH 8,5 com cerca de 40 a 60% de atividade relativa. A temperatura ótima de atividade enzimática determinada como ideal foi de 60 a 65 °C, porém a enzima mostrou-se termoestável até 60 °C. Os testes do efeito de íons na reação enzimática amilolítica demonstraram que os íons Cu+2, Zn+2, Al+2 e Na+2 comportaram-se como inibidores da atividade. O íon Mn+2 destacou-se por potencializar em...
Keywords: Biotechnology; Biotecnologia; Amilase; Fermentação